The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1289/ehp.1510194
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Overexpression of Aryl Hydrocarbon Receptor Repressor (AhRR) and AhR-Mediated Induction of CYP1A1, Cytokines, and Acute Toxicity

Abstract: Background:The aryl hydrocarbon receptor repressor (AhRR) is known to repress aryl hydrocarbon receptor (AhR) signaling, but very little is known regarding the role of the AhRR in vivo.Objective:This study tested the role of AhRR in vivo in AhRR overexpressing mice on molecular and toxic end points mediated through a prototypical AhR ligand.Methods:We generated AhRR-transgenic mice (AhRR Tg) based on the genetic background of C57BL/6J wild type (wt) mice. We tested the effect of the prototypical AhR ligand 2,3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 67 publications
7
42
0
Order By: Relevance
“…In addition to BPA (404) (32) (433), gene expression and secretion of inflammatory factors from adipocytes has been reported to increase in response to TCDD (195) (235) (34) (292) (203), PCB-77 (34) PCB-126 (203), and DEHP (62). Moreover, infiltration of macrophages into AT, a pathway associated with obesity-induced insulin resistance, has been reported as a result of exposure to DEHP (a phthalate) (62) HBCD (a BFR) (431), and TCDD (415). …”
Section: Effects Of Pops On At Functionmentioning
confidence: 99%
“…In addition to BPA (404) (32) (433), gene expression and secretion of inflammatory factors from adipocytes has been reported to increase in response to TCDD (195) (235) (34) (292) (203), PCB-77 (34) PCB-126 (203), and DEHP (62). Moreover, infiltration of macrophages into AT, a pathway associated with obesity-induced insulin resistance, has been reported as a result of exposure to DEHP (a phthalate) (62) HBCD (a BFR) (431), and TCDD (415). …”
Section: Effects Of Pops On At Functionmentioning
confidence: 99%
“…AHRR has been described as a negative tissue-specific regulator of mCYP1A1 expression [43, 44]. Its overexpression in transgenic mice suppresses the mCYP1A1 induction in lung, spleen, and adipose tissue [45]. Moreover, it has been suggested that rat CYP1A1 regulates its own expression because it catalyzes the removal of AHR agonists and thus decreases the activation of this pathway [46, 47].…”
Section: Downregulation Of Cyp1a1mentioning
confidence: 99%
“…On the other hand, CYP1A1 induction by AhR activation is not always enhanced in AhRR KO mice [11], and thus, the function of AhRR has remained a subject of dispute. Interestingly, in AhRR transgenic mice, which we produced previously, the basal expression of CYP1A1 in the kidney was increased compared to wild-type mice [14], suggesting that AhRR may have a positive regulatory function in murine kidneys. AhRR has been reported not to suppress CYP1A1 expression in human skin fibroblasts [16].…”
Section: Discussionmentioning
confidence: 99%
“…Equal amounts of protein were loaded, separated via SDS-PAGE and transferred onto polyvinylidene difluoride membranes. The blocked membranes were incubated with the following primary antibodies: anti-AhRR [14], anti-C/EBPα (Santa Cruz Biotechnology, Dallas, TX, USA), anti-C/EBPβ (Santa Cruz Biotechnology), anti-PPARγ (Santa Cruz Biotechnology) and anti-α-tubulin (Sigma-Aldrich). Then, the membrane was incubated in solutions with peroxide-conjugated secondary antibodies (Thermo Fisher Scientific) and was visualized using peroxide substrates (SuperSignal West Dura, Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation